The effect of nano propolis on surface color changes of nanohybrid composite resins - Christian, Bernardus Daniel; Serena, Derice Putri Nourah; Widjiastuti, Ira; Setyabudi (Conservative Dentistry Journal, 2024)
Background: Nanohybrid composite resins have many advantages, but one disadvantage is their absorbent nature which can lead to discoloration. Phenols and flavonoids in nano propolis cause diffusion and affect the matrix and pigments of nanohybrid composite resins. The accumulation of reduction-oxidation reactions causes new compounds of nanohybrid composite resins to occur so that they have different colors. Objective: The study was conducted to determine the changes in surface color of nanohybrid composite resin after immersion in nano propolis at 5% concentration. Methods: Research experimental laboratory method with pre and post test design was applied to 25 nanohybrid composite resin fruit samples of size (5x5x1.5) mm embedded in bovine incisive, then immersed in 5% nano propolis and 25 ml of distilled water at 37oC for five days. The color change (ΔE) was measured with a DSLR camera and processed with Adobe Lightroom Classic software in CIE L*a*b* format. Results: The anova test on ΔE in the data showed the p-value of sphericity assumed was smaller than 0.05. There is a difference in the average measurement results on the first day to the fifth day in the treatment group. Independent t-test of control and treatment data showed a significant difference in measurement results. The results of the post hoc test with the Tukey method showed that the treatment groups at 4x24 hours and 5x24 hours did not have significant differences. P-value at 4x24 hours and 5x24 hours was 0.957. Conclusion: There was a change in the surface color of the nanohybrid composite resin after being immersed in a nano-solution of propolis with a concentration of 5%.